Cu (II) Recovery with Solid Phase Extraction Technique Using Silica Adsorbent from Rice Husk ash - Chitosan - Nanang Tri Widodo; Ani Mulyasuryani; Akhmad Sabarudin (Natural B, Journal of Health and Environmental Sciences, 2014)
Copper compounds are widely used in modern industry. Many of these compounds are dumped into the surrounding environment. Copper is toxic and able to cause some diseases. The aim of this study is to create solid phase from natural material that applied to the solid phase extraction method as an alternative method to decrease the level of copper from water bodies and able to preconcentrate Cu2+ ions, reaching the detectable level. Silica from rice husk ash modified with chitosan result in an adsorbent that can improve the adsorption of Cu2+. Interaction of Cu2+ with solid phase silica–chitosan is based on data of Fourier Transform Infrared (FTIR), Scanning Electron Microscope (SEM) and Transmission Electron Microscope (TEM). The percentage recovery of Cu2+ each the Cu2+ concentration of 0.05, 0.1 and 0.2 ppm is 55.32%, 54.35% and 71.94%. The adsorbent has ability to adsorb Cu2+ is 100%.